The role of leadership and academic atmosphere in private universities in improving the quality of lecturers: Study at Warmadewa University - Suryawan, KM. Ada Gelgel; Gani, Abdul Juli Andi; Hanafi, Imam (International research journal of management, IT and social sciences, 2020)
The purpose of this study is first, to analyze and describe the quality level of lecturers. Second, to analyze the effect of the leadership role on improving the quality of lecturers. Third, to analyze the influence of the academic atmosphere on improving the quality of lecturers. This research used quantitative methods with descriptive analysis and classic assumption test, multiple linear tests, and hypothesis testing. The research was conducted at Warmadewa University, Denpasar. The findings of this study indicated that first, the quality of lecturers at the University of Warmadewa was good, and this could be seen from several indicators including academic qualifications (all lecturers were qualified from S2 and S3). Based on academic positions, all of them had academic positions. In terms of lecturer certification, it is shown that 20% were not certified and 80% were certified. In the indicators of writing scientific papers, it is shown that on average 85% of the lecturers already had articles in international and national journals as well as international and national seminar proceedings.